Histological alterations and oxidative stress parameters in common carp (Cyprinus carpio L. 1758) from blooming Hídvégi Pond, Hungary - Drobac Backović, Damjana; Tokodi, Nada; Marinović, Zoran; Ács, András; Šćekić, Ilija; Lujić, Jelena; Svirčev, Zorica (Biologia Serbica, 2023)
Accelerated eutrophication and climate change has led to more frequent blooming of cyanobacteria and the appearance of cyanotoxins worldwide. Because they are at the top of the aquatic food chain, fish can be exposed to cyanobacteria and their toxic metabolites. Thus, as one of the most complex organisms that inhabit aquatic ecosystems, fish can be good bioindicators of water pollution. The objective of this study was to assess several biomarkers in common carp (Cyprinus carpio L. 1758) from Hídvégi Pond (Hungary) sampled in June 2019: including histopathological changes of individual fish organs, biotransformation enzymes and oxidative stress parameters. An attempt was made to verify whether findings could be associated with previously reported cyanotoxin exposure. The results showed that DNA fragmentation was not observed; cytochrome P450 1A enzyme activity was higher in the testes, glutathione-S-transferase was significantly lower in the liver and ovaries, lipid peroxidation levels were high in all organs except the testes (with the highest level in the liver and gills); catalase and superoxide dismutase activity were significantly lower in the liver; total and Se-dependent glutathione peroxidase activity was significantly lower in the liver, while significantly higher activity was measured in the testes; glutathione reductase activity was increased in the liver and testes of C. carpio caught from Hídvégi Pond. Intense lipid peroxidation and changes in the activity of antioxidant enzymes indicate that fish from Hídvégi Pond were exposed to oxidative stress, potentially induced by cyanobacteria and/or their metabolites. Additionally, histopathological alterations were observed in the liver, kidneys and gills of fish, and specific damage to these organs could be directly linked to the action of hepatotoxic cyanotoxins. Therefore, it is likely that cyanobacteria and cyanotoxins have a detrimental effect on fish, as well as on other organisms including humans. Hence it is necessary to monitor cyanobacteria, cyanotoxins, and their effects on other organisms, and develop biomarkers capable of directly monitoring toxicity and pollution in the environment.